Analysis and optimization of cooperative wireless networks - Tran, Phuong T (ProQuest Dissertations & Theses, 2013)
Recently, cooperative communication between users in wireless networks has attracted a considerable amount of attention. A significant amount of research has been conducted to optimize the performance of different cooperative communication schemes, subject to some resource constraints such as power, bandwidth, and time. However, in previous research, each optimization problem has been investigated separately, and the optimal solution for one problem is usually not optimal for the other problems. This dissertation focuses on joint optimization or cross-layer optimization in wireless cooperative networks. One important obstacle is the non-convexity of the joint optimization problem, which makes the problem difficult to solve efficiently. The first contribution of this dissertation is the proposal of a method to efficiently solve a joint optimization problem of power allocation, time scheduling and relay selection strategy in Decode-and-Forward cooperative networks. To overcome the non-convexity obstacle, the dual optimization method for non-convex problems [1], is applied by exploiting the time-sharing properties of wireless OFDM systems when the number of subcarriers approaches infinity. The second contribution of this dissertation is the design of practical algorithms to implement the aforementioned method for optimizing the cooperative network. The difficulty of this work is caused by the randomness of the data, specifically, the randomness of the channel condition, and the real-time requirements of computing. The proposed algorithms were analyzed rigorously and the convergence of the algorithms is shown. Furthermore, a joint optimization problem of power allocation and computational functions for the advanced cooperation scheme, Compute-and-Forward, is also analyzed, and an iterative algorithm to solve this problem is also introduced.